Pedagogical liberalism - Pintar, Željka (Array, 2021)
This paper deals with the characteristics of the modern pedagogical paradigm, especially that of early and preschool education which emerged in the social context of liberal ideology. In order to better understand the educational model it promotes, the introductory part of the paper discusses the basic principles and starting points of the liberal social concept. The paper problematizes the diversity of the liberal conception of upbringing and education in relation to advocacy of the socialist social concept. The concept of self-regulated learning in the context of upbringing and education of an early and preschool child is observed. Common syntagms of the modern educational paradigm related to early and preschool education, such as the one about space as a third educator, are problematized. In this context, it is considered who or what constitutes basic pedagogical capital. The role of educators in the educational process, as well as the importance of adults in education in general are considered, and from this position the process of self-regulated learning is observed. The importance of self- observation in the current educational paradigm and recognition of the need for its ideological improvement in order to adequately contribute to children's upbringing and education is pointed out.